Platelets and Factor XI Bypass the Contact System of Blood Coagulation - Walsh, Peter N. (Thrombosis and Haemostasis, 1999)
Factor XI is a plasma glycoprotein (concentration ∼30 nM) that was first identified by Rosenthal et al1 as a plasma coagulation factor deficiency in patients with abnormal hemostasis, particularly common among Ashkenazi Jews.2,3 In spite of recent advances in our understanding of the structure of factor XI and its gene, the structure-function relationships of the protein, and the molecular genetics of factor XI deficiency, considerable confusion about the physiologic role and clinical relevance of factor XI has arisen from both clinical and biochemical observations. One problem arises from the fact that, until recently, the only known pathway for activation of factor XI involved proteolytic activation by factor XIIa and interactions with coagulation proteins of the contact phase of blood coagulation.4-7 The problem arose from the clinical observation that patients with deficiencies of factor XI are subject to bleeding complications, whereas patients with deficiencies of the contact proteins are not.2,3,8-13 A related unanswered question concerns the lack of correlation in many reported patients between plasma levels of factor XI and the severity of clinical bleeding manifestations.2,3,8,9,13-15 In addition, some patients with severe factor XI deficiency experience significant bleeding complications, whereas others appear to be hemostatically normal. These clinical and biochemical observations have motivated investigations focused on alternative mechanisms for activation of factor XI independent of contact phase protein.19-22 Additional studies have focused on the identification and characterization of platelet factor XI, which is postulated to be an alternative splicing product of the factor XI gene. Platelet factor XI is present in platelet membranes and might substitute for plasma factor XI in hemostasis and account for the absence of bleeding complications in some patients with severe plasma factor XI deficiency.14,16-18,23-26 Studies addressing these two important and related problems are presented and discussed in this chapter.